Insufficient response to mRNA SARS-CoV-2 vaccine and high incidence of severe COVID-19 in kidney transplant recipients during pandemic - Reischig, Tomas; Kacer, Martin; Vlas, Tomas; Drenko, Petr; Kielberger, Lukas; Machova, Jana; Topolcan, Ondrej; Kucera, Radek; Kormunda, Stanislav (American journal of transplantation, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) mRNA vaccination may fail to sufficiently protect transplant recipients against coronavirus disease 2019 (COVID-19). We retrospectively evaluated COVID-19 in kidney transplant recipients (n = 226) after BNT162b2 mRNA vaccine administration. The control group consisted of unvaccinated patients (n = 194) during the previous pandemic wave. We measured anti-spike protein immunoglobulin G (IgG) levels and cellular responses, using enzyme-linked immunosorbent spot assay, in a prospective cohort after vaccination (n = 31) and recovery from COVID-19 (n = 19). COVID-19 was diagnosed in 37 (16%) vaccinated and 43 (22%) unvaccinated patients. COVID-19 severity was similar in both groups, with patients exhibiting a comparable need for hospitalization (41% vs. 40%, p = 1.000) and mortality (14% vs. 9%, p = .726). Short posttransplant periods were associated with COVID-19 after vaccination (p < .001). Only 5 (16%) patients achieved positive SARS-CoV-2 IgG after vaccination, and 17 (89%, p < .001) recovered from COVID-19 (median IgG levels, 0.6 vs. 52.5 AU/ml, p < .001). A cellular response following vaccination was present in the majority (n = 22, 71%), with an increase in interleukin 2 secreting T cells (p < .001). Despite detectable T cell immunity after mRNA vaccination, kidney transplant recipients remained at a high risk of severe COVID-19. Humoral responses induced by vaccination were significantly lower than that after COVID-19.
Keywords: syntetické vakcíny; vakcíny proti COVID-19; COVID-19; lidé; Pandemics; clinical research / practice; Vaccines, Synthetic; kidney transplantation / nephrology; prospektivní studie; mRNA Vaccines; transplantace ledvin; infection and infectious agents - viral; messenger RNA; Incidence; RNA, Messenger; Kidney Transplantation; infectious disease; SARS-CoV-2/COVID-19; retrospektivní studie; Humans; vakcína BNT162; příjemce transplantátu; Antibodies, Viral; Prospective Studies; mRNA vakcíny; Transplant Recipients; COVID-19 Vaccines; pandemie; SARS-CoV-2; vaccine; protilátky virové; incidence; Retrospective Studies; BNT162 Vaccine